1991
DOI: 10.1104/pp.97.3.1253
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic Acid Induces Tuberization of Potato Stolons Cultured in Vitro

Abstract: The aim of the study was to assess the potential in vitro effects of jasmonic acid and kinetin on tuberization of potato (Solanum tuberosum). Of the two, the former was by far the stronger In vitro promoter of stolon tuberization. Number of tubers induced per stolon, tuberization rate, and final tuber weight were higher by factors of 2.8, 2.3, and 6.4, respectively. Bioassay sensitivity of jasmonic acid, measured in terms of the point at which the concentration for inducing tuberization was saturating, was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 14 publications
4
60
0
2
Order By: Relevance
“…LOX belong to the group of genes that have been shown to be expressed early during potato tuber formation [22,24], and LOX secondary products, such as jasmonic acid and its derivative tuberonic acid, have been shown to induce tuberization in vitro [25,26]. Interestingly, the most abundant LOX activity detected was of 9-positional specificity and this activity increases upon wounding [27].…”
Section: Introductionmentioning
confidence: 99%
“…LOX belong to the group of genes that have been shown to be expressed early during potato tuber formation [22,24], and LOX secondary products, such as jasmonic acid and its derivative tuberonic acid, have been shown to induce tuberization in vitro [25,26]. Interestingly, the most abundant LOX activity detected was of 9-positional specificity and this activity increases upon wounding [27].…”
Section: Introductionmentioning
confidence: 99%
“…Jasmonates are also potential stimulators for the expression of vegetative storage protein genes [20]. It is also reported that JA's are effective during in vitro microtuberization in addition to playing an important role in the development of vegetative storage organs [16,19,[21][22][23][24]. However, JA's influence on microtuber development and its relationship with other growth regulators are still not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Two drops of Tween-20 were then added and left to wait in a 10% NaOCl solution for 7-8 minutes, after which the shoot tips were washed with distilled water 3 times for sterilization [18][19][20][21][22][23][24][25][26][27][28]. Shoot tip explants obtained from sterilized shoots were then planted in a modified Murashige and Skoog (MS) medium [30].…”
Section: -4 Weeksmentioning
confidence: 99%
“…Jasmonate applications also have antixenotic effects on feeding preferences and oviposition site selection of certain herbivores Bruinsma et al 2007;van Dam 2008) and increase airborne volatiles, which attract natural enemies (Thaler et al 2001;Bruinsma et al 2009) and pollinators (Radhika et al 2010). In addition to their role in induction of plant defenses, jasmonates are involved in the activation of nutritive sinks (Creelman and Mullet 1997;Anrold and Schultz 2002;Meuriot et al 2004;Babst et al 2005) by regulating certain genes that encode vegetative storage proteins (Anderson 1991;Meuriot et al 2004) and that are involved in tuber formation (Pelacho and Mingo-Castel 1991;Koda 1992;Staswick 1994). Treatment of Medicago sativa with methyl jasmonate increases nitrogen partitioning to vegetative sinks (Meuriot et al 2004).…”
Section: Introductionmentioning
confidence: 99%